Salon éclaté. - Parent, Francis; Plazy, Gilles; Seuphor, Michel; Xuriguera, Gérard (Paris : Yves Cothouit, 1980)
Ado ; Amor, Ouanes ; Art, Raymond ; Artozoul ; Assemat, Pierre ; Atila, Biro ; Aubert, Michel ; Avoscan, Ivan ; Bailly, Jean-Jacques ; Barbu, Louise ; Batbedat, Vincent ; Bellomo, Lillo ; Benedito, Concha ; Bertrand, Ode ; Bezie, Charles ; Bignolais, Gérard ; Bigot, Guy ; Bilweis, Jean-Louis ; Boniface, Odile ; Boucraut, Thérèse ; Bourguignon, Claude ; Bozzolini, Silvano ; Breschand, Maurice ; Calos, Ninos ; Canes, José ; Castano, Jorge ; De Castreras, Christiane ; Marquet, Andrée ; Cehes, Claude ; Chamant, Marie ; Kin-Chung, Chan ; Chevallier, Jean-Marie ; Christiaens, Jean ; Teh-Chun, Chu ; Clement, Jean-Pierre ; Colvin, Marta ; Cornilleau, Jean-Loup ; Cupsa, Vicotr ; Derivery-Dupre-Perrot ; Delisle, Lisbeth ; Delmas, Igor ; Devade, Marc ; Martino, Gaetano Di ; Doideau, Annick ; Dotti, Franco ; Dromigny, Marie-Françoise ; Durand, Christiane ; Durand, James ; Eskenazi, Roger ; Espilit, Jean-Louis ; Fabra, Alberto ; Faif, Garry ; Falchi, Ettore ; Faublee, Michel ; Favresse, Marc ; Feraud, Albert ; Ferreira-Rocha, Raul ; Ferro, Sergio ; Furudoi, Koji ; Ghez, Gilles ; Gili, Marcel ; Gontard, Moris ; Greff-Davis, Yvonne ; Guanse, Antonio ; Guinot, Georges ; Hoenraet, Luc ; Holley, Francine ; Hug, Jean-Claude ; Ichikawa, Yo ; Iizuka, Hachiro ; Jaulin, Louis ; Jonquieres, Eduardo ; Kano, Minoru ; Kiras, Jean ; Koch, Gérard ; Kozo ; Kozuru, Koïchi ; Kramer, Lukas ; Laforest, Frantz ; Lago-Rivera, Antonio ; Laks, Victor ; Lardeur, Gérard ; Bars, Charles Le ; Ledannois, Jean-Marie ; Leinardi, Ermanno ; Lemos, Luis ; Provost, Jean-Paul Le ; Licata, Riccardo ; Lipsi, Morice ; Lozano, Agueda ; De Lussigny, Guy ; Mandeville, Bernard ; Marx, Ellen ; Melo, Francisco ; Merklen, Lucifugus ; Milhaud, Daniel ; Millecamps, Yves ; Miotte, Jean ; Mitrofanoff, France ; etc.
biografie
Salon éclaté, Yves Cothouit, Paris, 13 oct - 15 nov 80
Frans
boek